Land Use Change Dynamics in Southern California: Does Geographic Elasticity Matter?. (March 2018) - Kim, Jae Hong; Hipp, John R.; Basolo, Victoria; Dillon, Harya S.
This article examines how municipal planning contexts can shape urban land use dynamics by investigating the parcel-level land use changes in a five-county Southern California metropolitan area between 1990 and 2005. An analysis, based on a multinomial logit model, shows that land use change patterns significantly vary by municipalities that were situated in heterogeneous planning contexts. More specifically, cities with limited ability to expand their jurisdictional boundaries are found to provide more recreational areas and urban open spaces, while restricting nonconventional land uses. However, no evidence of a shift from single-family to multifamily residential development is detected for such cities.